(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Anđa Petrović (1889–1914) was the daughter of Mita Petrović and the sister of Nadežda and Rastko Petrović, as well as violinist and painter Ljubica Luković and poets Draga Petrović and Milica Mišković. Anđa Petrović is remembered for her famous correspondence with Leo Tolstoy on the topic of the Austro-Hungarian annexation of Bosnia and Herzegovina. In this correspondence, Anđa revealed herself as a great patriot who believed that freedom could be won only through war and with the aid of great and powerful allies, such as Russia. For this reason, she also took upon herself the role of a diplomat, not allowing Tolstoy’s pacifism and idealism to turn her into a resigned person. Although the Russian writer turned a deaf ear to her pleadings for spreading awareness of the injustices inflicted upon the Serbian people, she did, undeniably, leave an impression on him in the sense that it was because of her that he wrote a treatise on the Serbian question. She left behind one published and several unpublished manuscripts, which are the topic of this paper. Her works are essayistic, historiographic, and literary in character. The essential topic they deal with is that of women in Serbian history, hence patriotism and feminism may be viewed as the main traits of her works. From familial and love affairs in the family of Prince Miloš Obrenović, with a focus on the relationship between Princess Ljubica and the Prince’s mistresses Petrija and Jelenka, to public speeches and essays on literature and women’s emancipation, and the story of her own nostalgia for her native region, Anđa’s opus, albeit partially preserved and incomplete, is essentially integral in terms of both theme and style. When it comes to the works that have not been preserved, it is possible to learn about them from the few available newspaper texts dedicated to this author. The goal of this paper is to analyze her literary oeuvre and to conduct research into the intertextuality that can be found in it. Owing to her lecture notes from her comparative literature lessons, it is possible to reconstruct the influences on her body of work. She paid special attention to the analysis of Shakespeare’s play Antony and Cleopatra, so it is possible to find a link with this play in Anđa’s portrayal of Princess Ljubica’s character.